Late HIV presentation among AIDS cases in Australia, 1992-2001 - Ann M. McDonald; Yueming Li; Gregory J. Dore; Hugo Ree; John M. Kaldor (Elsevier, 2003)
Abstract Objective: To describe time trends and demographic, exposure and clinical factors associated with late HIV presentation among notified AIDS cases diagnosed in Australia in 1992-2001. Methods: AIDS cases, diagnosed in Australia and notified to the National AIDS Registry, were included in the analysis. AIDS cases newly diagnosed with HIV infection within three months of AIDS diagnosis were defined as cases of late HIV presentation. Results: The percentage of AIDS cases with late HIV presentation increased significantly from 18% in 1992-96 to 33.1% in 1997 (adjusted odds ratio (AOR)=1.79, p<0.005) and to 49.6% in 2001 (AOR=3.01, p<0.005). Older age, having been born in Asia, a HIV exposure history of heterosexual contact or an 'other/undetermined' exposure and a diagnosis of PCP only or of multiple AIDS illnesses, were associated with late HIV presentation among AIDS cases diagnosed in 1992-96 and in 1997-2001, and among overseas‐born cases diagnosed in 1992-2001. In 1997-2001, a low CD4+ cell count was also associated with late HIV presentation. Among homosexually active men diagnosed with AIDS in 1997-2001, older age, a diagnosis of PCP or multiple AIDS illnesses and a low CD4+ cell count were associated with late HIV presentation. Conclusion: Predictors of late HIV presentation have remained substantially unchanged over time and among population subgroups, suggesting a need for innovation in HIV/AIDS testing and counselling strategies.